The update of the line positions and intensities in the line list of carbon dioxide for the HITRAN2020 spectroscopic database. (December 2021) - Karlovets, E.V.; Gordon, I.E.; Rothman, L.S.; Hashemi, R.; Hargreaves, R.J.; Toon, G.C.; Campargue, A.; Perevalov, V.I.; Čermák, P.; Birk, M.; Wagner, G.; Hodges, J.T.; et al.
Highlights: The new HITRAN2020 line list for all 12 naturally abundant isotopologues of carbon dioxide replaces the previous one from the HITRAN2016 edition. Evaluation of the HITRAN CO2 line lists by comparison to laboratory and atmospheric spectra below 8310 cm −1 was carried out. The updates made for the bands having mixed CDSD and UCL-IAO line intensities in the HITRAN2016 line list below 8000 cm −1 are presented. The CO2 bands in the 1.4- to 2.1-µm region were improved. New CO2 bands above 8000 cm −1 were added to the HITRAN2020 edition from the new high-temperature UCL-4000 12 C 16 O2 line list (ExoMol database) and the CRDS spectra for the 16 O 12 C 18 O isotopologue. The magnetic dipole 01111–00001 band of the 12 C 16 O2 isotopologue in the 3.3-µm region was introduced into HITRAN for the first time. Abstract: This paper describes the updates of the line positions and intensities for the carbon dioxide transitions in the 2020 edition of the HITRAN spectroscopic database. The new line list for all 12 naturally abundant isotopologues of carbon dioxide replaces the previous one from the HITRAN2016 edition. This update is primarily motivated by several issues related to deficient HITRAN2016 line positions and intensities that have been identified from laboratory and atmospheric spectra. Critical validation tests for the spectroscopic data were carried out to find problems caused by inaccuracies in CO2 line parameters. New sources of data were selected for the bands that were deemed problematic in the HITRAN2016 edition. Extra care was taken to retain the consistency in the data sources within the bands. The comparisons with the existing theoretical and semi-empirical databases (including ExoMol, NASA Ames, and CDSD-296) and with available experimental works were carried out. The HITRAN2020 database has been extended by including additional CO2 bands above 8000 cm −1, and magnetic dipole lines of CO2 were introduced in HITRAN for the first time by including the ν2 +ν3 band in the 3.3-µm region. Although the main topic of this article is line positions and intensities, for consistency a recent algorithm for the line-shape parameters proposed in Hashemi et al. JQSRT (2020) was reapplied (after minor revisions) to the line list. Graphical abstract: Image, graphical abstract